The Church of Our Lady at Scherpenheuvel (Bulletin KNOB, 1999)
The church of Scherpenheuvel was built from 1609 during the reign and with the support of Archdukes Albrecht and Isabella, who were personally closely involved in the adoration of the miraculous statue of the Virgin Mary. The church building forms the centre of the seven-cornered concentrically laid-out town square already designed for it, which at that time embodied the most modern views on ideal town planning.The dome-shaped church is built in an utterly modern Italian architectural language and its concept implies a complete break with the local tradition (Illustr. l, 2, 3). Until now the court architect of the Archduke and Archduchess, Wenceslas Cobergher, who had spent a long period in Rome, was considered to have provided the inspiration for the church building.Within the direct family context of the Archduke, however, we come across a building project of which the form language and meanings show strong similarity with Scherpenheuvel.On March 11, 1585 Carlo Emanuele I, duke of Savoie and Prince of Piemont, married his cousin, Catalina Michaela and younger sister of the Archduchess Infanta Isabella, in Zaragoza. When Catalina unexpectedly dies in 1597, the duke decides to bury her in the church of Mondovi, a Marian pilgrims' church designed on the basis of an oval-shaped central ground plan, which had been started a few years previously.It is likely that Albrecht was told about this project just before and during his honeymoon, when he stayed in the duchy of Savoie for some months. The occurrence of this architecture project within the family context of Archduke Albrecht makes it very likely that he had claimed a more prominent role for himself in the active design process of the church of Scherpenheuvel than was assumed until recently. Contemporary examples show that other monarchs also regarded this as an appropriate regal occupation and used these architectural designs to visualize their political aspirations.